2024
DOI: 10.1002/prot.26707
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the role of deleterious mutations at the dimeric interface of Toll‐like receptor interferon‐β related adaptor protein

Shailya Verma,
Revathy Menon,
Ramanathan Sowdhamini

Abstract: Toll‐like receptors (TLRs) are major players in the innate immune system—recognizing pathogens and differentiating self/non‐self components of immunity. These proteins are present either on the plasma membrane or endosome and recognize pathogens at their extracellular domains. They are characterized by a single transmembrane helix and an intracellular toll‐interleukin‐1 receptor (TIR) domain. Few TIRs directly invoke downstream signaling, while others require other TIR domains of adaptors like TIR domain‐conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We used multiple approaches for modelling proteins dimer, trimer, and tetramer complex. In a previous study from our lab, we had established the dimer model of TRAM protein using various parameters [39]. In one of the approaches, we used the TRAM MD stabilized structure as our starting dimer model and use protein docking algorithm to model the TRAM dimer and TRIF complex.…”
Section: Protein Modelling and Docking Of Trimer Complexmentioning
confidence: 99%
“…We used multiple approaches for modelling proteins dimer, trimer, and tetramer complex. In a previous study from our lab, we had established the dimer model of TRAM protein using various parameters [39]. In one of the approaches, we used the TRAM MD stabilized structure as our starting dimer model and use protein docking algorithm to model the TRAM dimer and TRIF complex.…”
Section: Protein Modelling and Docking Of Trimer Complexmentioning
confidence: 99%
“…To date, studies have shown that TLRs bear the responsibility of playing important roles in innate immunity in organisms (Verma et al, 2024). Innate immune cells, such as dendritic cells (DCs), are activated when the immune system detects microorganisms through a variety of receptors known as pattern recognition receptors (PRRs), which are encoded by germ-line genes and recognize a wide range of microbial structures (Wang et al, 2024).…”
Section: Introductionmentioning
confidence: 99%